Evaporated palm oil cracking to gasoline over zeolite catalysts - Siregar, Tirena Bahnur (Penerbit UTM Press, 2010)
The catalytic cracking of palm oil to gasoline over H–ZSM–5 and H–Beta was studied in fixed bed reactor operated at atmospheric pressure and weight hourly space velocity (WHSV) of 2.5 h–1. The reaction temperature was varied between 450°C to 525°C. The calcined catalysts were characterized using X–Ray Diffraction (XRD), Pyridine Adsorption–Infrared Spectrophotometry (Py–IR) and Nitrogen Adsorption (NA) methods. The liquid and gaseous products were analyzed using (FID) and (TCD) gas chromatography respectively. Increase in reaction temperature led to higher palm oil conversion. The highest conversion and gasoline selectivity obtained at 525°C were 96.12 wt% and 29.92 wt% respectively with H–ZSM–5. Although the conversion and the gasoline selectivity of both catalysts was high, but H–ZSM–5 performed better than H–Beta at all temperature range. Gasoline produced using H–ZSM–5 consisted mainly of naphthenes beside isoparaffins, olefins, aromatics and a small amount of paraffins, while the gasoline obtained by using H–Beta contained olefins, naphthenes, paraffins and aromatics. Gas was the major side product, which consisted mainly of C1–C3 for using H–ZSM–5 and C3–C4 compounds for using H–Beta.